The Growth of Galaxy Stellar Mass within Dark Matter Halos - Zehavi, Idit (2012)
We study the evolution of stellar mass in galaxies as a function of host halo mass, using the "MPA" and "Durham" semi-analytic models, implemented on the Millennium Run simulation. The results from both models are similar. We find that about 45% of the stellar mass in central galaxies in present-day halos less massive than ~10^{12} Msun/h is already in place at z~1. This fraction increases to ~65% for more massive halos. The peak of star formation efficiency shifts toward lower mass halos from z~1 to z~0. The stellar mass in low-mass halos grows mostly by star formation since z~1, while in high-mass halos most of the stellar mass is assembled by mergers. These trends are clear indications of "halo downsizing". We compare our findings to the results of the phenomenological method developed by Zheng, Coil & Zehavi (2007). The theoretical predictions are in qualitative agreement with these results, however there are large discrepancies. The most significant one concerns the amount of stars already in place in the progenitor galaxies at z~1, which is about a factor of two larger in both semi-analytic models. We also use the semi-analytic catalogs to test different assumptions made in that work, and illustrate the importance of smooth accretion of dark matter when estimating the mergers contribution. We demonstrate that methods studying galaxy evolution from the galaxy-halo connection are powerful in constraining theoretical models and can guide future efforts of modeling galaxy evolution. Conversely, semi-analytic models serve an important role in improving such methods.